2020
DOI: 10.1101/2020.05.02.20088872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Hydroxychloroquine and Chloroquine Safety Profiles – A Systematic Review and Meta-Analysis

Abstract: Background:Recently, chloroquine (CQ) and its derivative hydroxychloroquine (HCQ) have emerged as potential antiviral and immunomodulatory options for the treatment of 2019 coronavirus disease . To examine the safety profiles of these medications, we systematically evaluated the adverse events (AEs) of these medications from published randomized controlled trials (RCTs). Methods: We systematically searched PubMed, MEDLINE, Cochrane, the Cochrane Central Register of Controlled Trials (CENTRAL), EMBASE, and the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
1
11
0
1
Order By: Relevance
“…Two recent meta-analyses conducted by Ren et al and Wang et al found that patients taking chloroquine or hydroxychloroquine had more adverse events compared to patients assigned to placebo group. 64,65 Another meta-analysis published a couple of months ago by Sarma et al 66 found no association of hydroxychloroquine with virological cure, death or clinical worsening and safety in nCOV-2019 patients. Similar findings on hydroxychloroquine with or without azithromycin were observed from another meta-analysis of five trials which although did observe a trend but the results were not found to be statistically significant in terms of negative conversion of nCOV-2019 (odds ratio [OR] 1.95; 95%CI 0.19 to 19.73) and reduction in progression rate (OR 0.89 95%CI 0.58 to 1.37).…”
Section: F I G U R Ementioning
confidence: 99%
“…Two recent meta-analyses conducted by Ren et al and Wang et al found that patients taking chloroquine or hydroxychloroquine had more adverse events compared to patients assigned to placebo group. 64,65 Another meta-analysis published a couple of months ago by Sarma et al 66 found no association of hydroxychloroquine with virological cure, death or clinical worsening and safety in nCOV-2019 patients. Similar findings on hydroxychloroquine with or without azithromycin were observed from another meta-analysis of five trials which although did observe a trend but the results were not found to be statistically significant in terms of negative conversion of nCOV-2019 (odds ratio [OR] 1.95; 95%CI 0.19 to 19.73) and reduction in progression rate (OR 0.89 95%CI 0.58 to 1.37).…”
Section: F I G U R Ementioning
confidence: 99%
“…respectively [114]. Eljaaly et al searched PubMed and EMBASE databases for RCTs of adults comparing AE of HCQ with placebo for any indication.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the CQ and its derivatives can shorten the course of SARS-CoV-2, reduce the inflammatory responses to infection, inhibit the deterioration of pneumonia, improve lung imaging performance, and promote the negative conversion of the virus (Kearney, 2020;Li and Liu, 2020). However, recent reports show that treatment with HCQ is associated with numerous adverse effects in patients with COVID-19, such as frequent QTc prolongation, erythema multiforme, acute generalized exanthematous pustulosis (Bessiere et al, 2020;Delaleu et al, 2020;Mercuro et al, 2020;Monte Serrano et al, 2020;Ren et al, 2020b;Torjesen, 2020). On Jun 16, 2020, the US Food and Drug Administration revoked the emergency use authorization for chloroquine and hydroxychloroquine due to their lack of efficacy and safety concerns (http://www.…”
Section: Host Protein Targeted Medicinesmentioning
confidence: 99%